Dismissed, Dormant, and Deep-rooted Immigration Distractions and Undocumented College Students' Academic Experiences - Daniel Millán (SAGE Publishing, 2024)
Evolving or stagnant immigration laws and policies may distinctly shape the experiences of undocumented students by shifting access to rights or opportunities. I draw upon 30 interviews with college students in California to analyze how they encountered legal vulnerability. I argue that legal vulnerability can be dismissed, dormant, or deep-rooted, producing contrasting experiences. Inclusive state and institutional policies set the stage for some students to dismiss legal vulnerability and decouple vulnerability from their academic experiences. However, most encountered dormant legal vulnerability through awakened racist xenophobia following the 2016 presidential election and deep-rooted legal vulnerability via persistent uncertainty about their futures or worries over family. Distracted students lost focus, motivation, and study time, which impacted their classroom participation and overall academic performance. Yet, they attempted to improve their academic engagement with limited effectiveness. Altogether, I theorize the relationship between different types of legal vulnerability and undocumented students' college experiences.